Aerodynamics of the Partial Bounding Flight of a Diamond Dove (Geopelia cuneata) - Warfvinge,Kajsa (2012)
ABSTRACT Among small to medium-sized birds, intermittent flight is a common behavior, where pauses are inserted between wingbeats. This is believed to have the effect of changing the power output without having to change the wingbeat frequency. Small birds often perform bounding flight, where the wings are completely folded against the body during pauses, while larger birds can be found to glide with the wings fully outstretched between the periods of flapping. I have studied the partial bounding flight of the diamond dove (Geopelia cuneata); a flight characterized by approximately 2-3 wingbeats followed by a short period of gliding with the wings partly folded. The dove was observed to adjust wingspan during glides as well as the length of the gliding period to account for different needs for lift at different wind tunnel angles and air speeds. In total, 16 angle/air speed combinations have been studied. Using stereo PIV, I have also derived lift forces from the circulation of the main vortex structures, the tip vortices, observed in the wake behind the bird. In flapping flight, the strength of the circulation was highly dependent on air speed, while, during gliding, the patterns were weaker. While the lift generated during flapping flight was estimated to account for the full weight of the bird, gliding flight produced lift corresponding to 1/3-1/2 of the bird’s weight. Measuring the downwards velocity between the main vortex structures, span efficiency and flap efficiency could be estimated. While the calculated span efficiency was higher than other bird and bat species, flap efficiency was close to what is assumed in Pennycuick’s model of flapping flight.